From Hikayat Hang Tuah to Bharat Ek-Khoj: A Malay Culture Hero in an Indian Docudrama (KEMANUSIAAN The Asian Journal of Humanities, 2023)
Hang Tuah, the most illustrious warrior figure in Malay literature, is said to have lived in Malacca during the reign of Sultan Mansur Shah in the 15th century. The story of Hang Tuah has fascinated audiences for many centuries and continues to be retold and fashioned to attract modern audiences. This study traces the adaptation of Hang Tuah across different languages, cultures and media. It explores the adaptation of Hang Tuah by an Indian from India. The objective of this study is to analyse what transpires in the adaptation of a Malay literary text to an Indian docudrama and make a close analysis of Hang Tuah as a Malay culture hero based on Hikayat Hang Tuah. His qualities as a culture hero are discussed thoroughly according to the concept of a culture hero by Jerome Long. At the same time, this research allows the readers to go into the Indian mind, asking especially the director to explain why he decided to adapt Hang Tuah in his historical docudrama. This study article critically analyses the transformation of the Malay culture hero, Hang Tuah, in the literary text entitled Hikayat Hang Tuah to Hang Tuah in the docudrama entitled Bharat Ek-Khoj. The transformation is examined in the context of literature-to-film adaptation. The relation between the original source and the screen adaptations is also investigated.